Process management in high tech New Zealand firms - Wood, Lincoln; Lu, Q. (World Scientific Publishing Co, 2008)
There are three distinct functions in the product realization chain — product design, process design, and process execution; thus there are two interfaces (product design — process design; process design — process execution) rather than one (product-manufacturing). Case studies of four organizations manufacturing high-tech products in New Zealand are explored to study the organization of process design functions and success strategies. Similarities in structuring, relationships between functional groups, and the methods for product and process design implementation are investigated. De-coupling of process design functions occurs best with high volume production with stable process technology — an infrequent situation with high-tech NZ manufacturers.